Practical Life Book as a Media for Strengthening the Independence Dimension of Pancasila Student Profiles in Early Childhood - Nur Rochimah; Rina Syafrida; Nancy Riana; Feronica Eka Putri; Dewi Siti Aisyah; Ine Nirmala; Astuti Darmiyanti; Permadani Rona (S&Co Publishing, 2026)
The development of early childhood independence is a key component in implementing the Independent Curriculum, particularly in strengthening the Pancasila Student Profile. However, empirically validated and structured learning media targeting this dimension remain limited. This study aims to examine the effect of the Practical Life Book, a Montessori-based learning medium focused on real-life activities, on enhancing early childhood independence. Using a One-Group Pretest-Posttest design, the study involved 53 children from Pembina Karawang Kindergarten selected through purposive sampling. The independence instrument consisted of 27 observational items completed by teachers based on BSKAP guidelines. The intervention was conducted over 16 sessions across 8 weeks. Results from the Paired Sample t-Test showed a significant improvement (t = 33.154; p < 0.001), with mean scores increasing from 59.09 to 84.38. The effect size was very large (Cohen’s d = 4.554), N-Gain was moderate (0.524), and η² = 0.955 indicated a strong intervention effect. These findings suggest that the Practical Life Book is effective in strengthening early childhood independence within the Pancasila Student Profile framework and has practical implications for developing learning media aligned with the Independent Curriculum.